THE EFFECT OF LEARNING TECHNIQUE AND LOCUS OF CONTROL ON STUDENTS COMPETENCE IN TRANSLATING FROM GERMAN TEXT INTO INDONESIAN ( AN EXPERIMENT AT GERMAN STUDY PROGRAM OF MAKASSAR STATE UNIVERSITY - Mannahali, Misnah; Rasyid, Yumna (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
The aim of this research was to find out the effect of learning technique and Locus of Control on students competence in translating from German Text into Indonesian. The research was conducted at the fourth semester on German Study Program in the academic years 2013/2014. It was an eksprimental study with 2 x 2 factorial design. The sample was 40 students. It was divided into two groups, each group experiment consisting of 20 students where 10 students had Internal Locus of Control and 10 others had external Locus of Control. The data was collected by using two kinds of test : Locus of Control test and test of translating from German Text into Indonesian. ANAVA and Tukey test were used to analyse the data. The results of this research concludes that generally Jigsaw learning technique was more effective than STAD learning technique, that is : 18,65 > 17,35. The result of this research also conclude that, the students who have internal Locus of Control when following lectures with STAD learning technique is higher ( 20,2 ) than Jigsaw learning technique ( 17,1 ). On the contrary students with external Locus of Control showing that Jigsaw learning technique (20,2) is better than STAD learning technique ( 14,5 ).The finding that Jigsaw and STAD learning technique can be used in teaching translation, however in choosing the teaching technique studentsâ Locus of Control should be considered.